Relationship of Classroom Behavior, Absenteeism, Truancy, Exclusion, and Academic Achievement: A Review in the Saudi Arabian Context (المجلة الدولية للبحوث العلمية, 2025)
School-related risk behaviors, such as absenteeism, lateness, truancy, and exclusions, are critical yet understudied issues in Saudi Arabia. This systematic review investigates the relationship between these behaviors and academic achievement in Saudi Arabian secondary schools. Drawing on 40+ studies from last five years (2019–2024), the review synthesizes quantitative and qualitative evidence to explore the prevalence, factors, and impact of school-related risk behaviors on academic outcomes. Findings reveal a strong negative correlation between absenteeism, lateness, truancy, and academic achievement, with socio-cultural, institutional, and individual factors playing significant roles. The study concludes with evidence-based recommendations for policymakers and educators to address these behaviors and improve academic success in Saudi Arabia.